The efficacy of ingesting water on thermoregulatory responses and running performance in a warm-humid condition - Che Muhamed, A. M.; Yusof, H. A.; Stannard, S. R.; Mündel, T.; Thompson, M. W. (Frontiers in Physiology, 2019)
The understanding that fluid ingestion attenuates thermoregulatory and circulatory stress during exercise in the heat was based on studies conducted in relatively dry (~50% RH) environments. It remains undetermined whether similar effects occur during exercise in a warm and more humid environment, where evaporative capacity is reduced. Nine well-trained, unacclimatised male runners were randomly assigned to perform four experimental trials where they ran for 60 min at an intensity of 70% VO2max followed by an incremental exercise test until volitional exhaustion. The four trials consisted of non-fluid ingestion (NF) and fluid ingestion (FI) in a warm-dry (WD) and warm-humid condition (WH). Time to exhaustion (TTE), body temperature (Tb), whole body sweat rate, partitional calorimetry measures, heart rate and plasma volume were recorded during exercise. There was no significant difference in Tb following 60 min of exercise in FI and NF trial within both WD (37.3°C ± 0.4 vs. 37.4°C ± 0.3; p > 0.05) and WH conditions (38.0°C ± 0.4 vs. 38.1°C ± 0.4; p > 0.05). The TTE was similar between FI and NF trials in both WH and WD, whereas exercise capacity was significantly shorter in WH than WD (9.1 ± 2.8 min vs. 12.7 ± 2.4 min, respectively; p = 0.01). Fluid ingestion failed to provide any ergogenic benefit in attenuating thermoregulatory and circulatory stress during exercise in the WH and WD conditions. Consequently, exercise performance was not enhanced with fluid ingestion in the warm-humid condition, although the humid environment detrimentally affected exercise endurance.